(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The development of auditory speech perception plays a critical role in language acquisition and communication, influencing how children learn and interact with others. This article focuses on identifying and exploring strategies that can support the growth of auditory speech perception, particularly in children facing challenges such as speech and language delays, hearing impairments, or those learning a non-native language. Educators can utilize these methods to enhance students’ language abilities, ensuring more effective learning outcomes across diverse educational contexts.